Coexistence of homologous-type carcinosarcoma of the cervix with undifferentiated carcinoma of the endometrium: A case report with Immunohistochemical analysis and literature review - Giovanna Giordano; Elena Ferioli; Anna Maria Rodolfi; Serena Madaro; Roberto Berretta (Elsevier, 2022)
We report a case of undifferentiated carcinoma of the endometrium associated with malignant mixed Müllerian tumour of the uterine cervix. Immunohistochemical analysis with multiple markers was performed to demonstrate the coexistence of highly two aggressive components in the same uterus. Clinical data were collected and followed up, and a careful literature review was performed to establish the occurence of these components in a uterine malignancy.